Il marketing della moda Temi emergenti nel tessile-abbigliamento - Burresi, Aldo (Strumenti per la didattica e la ricerca, 2005)
In light of the notoriety and the central role of Tuscan companies of the fashion sector, this publication - the result of the work of the research group of the Marketing Area of the Faculty of Economics of the University of Florence, and of the relationships intertwined by the research group with entrepreneurs and local institutions - intends to address the marketing problems of the fashion system, highlighting the elements of specificity and differentiation. On the basis of the knowledge acquired in the constant comparison with the managers of the sector, the authors identify emerging marketing themes to construct, starting from them, specific research paths for fashion marketing. The identified topics concern the study of the variety and variability of consumer behaviour, the analysis of fashion as a transversal phenomenon that affirms itself in luxury goods, and finally the interpretation of the co-evolutionary dynamics of consumer needs and company skills in a logic of continuous innovation.